Morphological comparisons of the Indo-West Pacific scorpionfish, Parascorpaena aurita, with a closely related species, P. picta, with first records of P. aurita from East Asia (Scorpaeniformes: Scorpaenidae) - Motomura, Hiroyuki; Sakurai, You; Senou, Hiroshi; Ho, Hsuan-Ching (Zootaxa, 2009)
The poorly known scorpionfish Parascorpaena aurita is redescribed on the basis of 96 specimens from the Indo-Pacific and compared in detail with a closely related species, P. picta. The two species can be distinguished from other congeners by lacking a suborbital spine below the eye and having usually 17 or 18 pectoral-fin rays. Examination of a large number of specimens of each species revealed that P. aurita differs from P. picta in a number of scale counts and morphometrics, and morphology of the suborbital and interorbital ridges, and occiput. Previously published photographs and/or specimen lists identified as P. picta included both species. Parascorpaena aurita is widely distributed in the IndoPacific, including East Asia (first records), whereas P. picta is restricted to Southeast Asia and Australia.